2019
DOI: 10.1164/rccm.201805-0825oc
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cytomegalovirus Immunity in Idiopathic Pulmonary Fibrosis Lung Transplant Recipients with Short Telomeres

Abstract: As the short telomere defect has been linked to the pathogenesis of IPF in some cases, our data indicate that impaired CMV immunity may be a systemic manifestation of telomere-mediated disease in these patients. Identifying this high-risk subset of lung transplant recipients has implications for risk assessment, management and potential strategies for averting posttransplant CMV morbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 51 publications
5
86
0
2
Order By: Relevance
“…The high frequency of telomere defects in IPF and the prevalence of this disease make IPF the most common of the human short telomere phenotypes. A subset of adult IPF patients show extrapulmonary short telomere syndrome features including bone marrow failure, immunodeficiency, and liver disease; their recognition is critical for the diagnosis and management of these patients (18,21,(41)(42)(43)47).…”
Section: Telomerase Is Limitingmentioning
confidence: 99%
“…The high frequency of telomere defects in IPF and the prevalence of this disease make IPF the most common of the human short telomere phenotypes. A subset of adult IPF patients show extrapulmonary short telomere syndrome features including bone marrow failure, immunodeficiency, and liver disease; their recognition is critical for the diagnosis and management of these patients (18,21,(41)(42)(43)47).…”
Section: Telomerase Is Limitingmentioning
confidence: 99%
“…One possible explanation for these findings is an impaired ability of IPF patients on IST to control EBV chronic infection. We previously demonstrated an increased susceptibility to CMV, another herpesvirus infection in patients with IPF and short telomeres in association with impaired viral immunity posttransplant, possibly related to changes in T cell immunity . In this historical cohort, blood samples were not available for all patients to assess telomere length in those who developed PTLD.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years it has become clear that the IPF population is enriched for short telomeres in >50% of patients, with ≈12% having germline mutations in telomerase and the telomere maintenance genes . We recently have shown that IPF LTRs with short telomeres have increased susceptibility to reactivation of the β‐herpesvirus, cytomegalovirus (CMV), with impaired CMV‐specific T cell immunity compared to age‐matched non‐IPF LTRs . Based on these findings, we hypothesized that IPF LTRs would have increased susceptibility to EBV‐associated PTLD in the setting of IST.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus not surprising that telomeropathies are enriched among lung allograft recipients. In this issue of the Journal, Popescu et al report that the same lung transplant recipients likely to have CMV prophylaxis discontinued secondary to telomere-related leukopenia may also be at greatest risk for uncontrolled CMV infection (9). In this cohort, IPF patients with short peripheral blood leukocyte telomeres had a 9-fold higher risk of CMV relapse compared to a matched control cohort of non-IPF lung transplant recipients, despite receiving similar durations of CMV prophylaxis.…”
mentioning
confidence: 85%